Le brouillage des frontières de la société salariale dans les Amériques et au-delà : une lecture des transformations du travail dans un globalising world - Christian Azaïs (IdeAs)
The labour crisis is analysed through two processes, standardisation and differentiation, the main characteristics of a globalising world. This can be appreciated through the blurring borders of wage earners, in both Northern and Southern societies, phenomenon which is taken into account through the concept of hybridisation. It reflects the entanglement of various forms of insertion of individuals into the labour market, occurring even for a single individual. The tendency towards workers' flexibilisation and precarisation is no longer the characteristic attribute of workers from the South: even the highly qualified, from South to North, are concerned. This general movement comes along with the emergence of a grey zone surrounding the employment relationship, an in-between zone that makes obsolete traditional dichotomies such as formal/informal labour; worker/unemployed; qualification/social protection, acting as an invitation for researchers to dwell upon the pertinence of categories. Such an evolution is characteristic of what we have characterised as a globalising world.Nowadays, the guaranties linked to the exercise of a profession, social rights, social protection are being affected and require a new analysis of labour and wage earning, because the ethnocentric form inherited from developed countries has become blatantly inadequate. Possibly more than ever, it has become difficult to distinguish the contours of employment and situations of dependency from those of autonomy at work, a sign that the borders of wage-earning societies tend to enlarge and to decompartmentalize, opening vast perspectives for research. These are some of the issues this text deals with to reach the conclusion that the crisis currently affecting labour is not cyclical; it is a durable one and any foreseeable solution is uncertain.